Education in Southeast Asia: Shaping the Asian Intellectuals - Padilla-Valdez, Nena (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2018)
With the view that the quality of human resource is the greatest transformational assest, the education of the Asian region strives in building a critical mass of k-economy citizens. Stimulating the educational system to move toward this direction resonates the seriousness of Asian institutions in seiving their traditions, overcoming their intricacies, and embracing uncertainties with positive anticipation. The presence of a critical mass of  academics postulates the urgency of changing organizational needs, and correspondingly increasing their absorptive capacity as  they respond to the intense competitive pressures being generated by an increasingly global economy. This paper explores the transitional changes the education system have rendered to boost regional integration. More specifically, it highlights the initiatives higher education institutions have adapted as they align their development thrusts to regional and national expectations. Likewise, it challenges local intellectuals to develop a macro perspective of flexibility while the changing educational priorities converge toward acceptable global practice.